Recent developments in gold-catalyzed cycloaddition reactions - López, Fernando; Mascareñas, José L. (Beilstein Journal of Organic Chemistry, 2011)
In the last years there have been extraordinary advances in the development of gold-catalyzed cycloaddition processes. In this review we will summarize some of the most remarkable examples, and present the mechanistic rational underlying the transformations.
Keywords: alkene; alkyne; allene; catalysis; cycloaddition; gold